Assessing Listening Comprehension Skills in Indonesian Islamic Higher Education EFL Classrooms: Current Practices, Challenges and Solutions - Rasyid, Muhammad Nur Akbar; Rauf, Masykur; Junaid, Syahruni; Nur, Serliah; Syukur, Helmi (Indonesian TESOL Journal, 2023)
The present study aims to examine the current practices, constraints, and potential enablers when assessing students' listening skills in Indonesian Islamic higher education EFL classrooms. This study used a qualitative approach with a case study research design. The selection of the participants used purposive sampling. The study used interviews as a data gathering technique, involving six EFL lecturers in one Indonesian Islamic higher education institution in South Sulawesi. The findings show participants’ awareness of the various alternative methods to assess students’ listening skills. However, their discussions tend to focus on what is easiest to use as opposed to what matters most for students’ listening skills. Furthermore, participants’ descriptions of EFL lecturers’ constraints in assessing listening skills encompass various educational aspects, which could be classified into resources and practical constraints. The former includes a lack of representative language laboratories and learning resources for conducting quality listening assessment practices. The latter relates to time constraints, auditory surroundings, and designing and developing listening assessment instruments. Therefore, the participants raised several key strategies to enhance quality listening assessment practices, ranging from resources to practical strategies. This includes a high quality and sufficient quantity of educational resources, the use of diverse and authentic assessment tasks, and more collaborative work to share best practices and experience in conducting quality listening assessment practices. These findings imply the need for reformulation of existing practices and policies related to foreign language assessment that could have significant impacts on EFL students, teachers, and classrooms.